PHARMACOLOGICAL SUPPORT ORGANIZATION OF ТВ PATIENTS IN SMOLENSK REGION - N. A. Pavluchenkova; A. V. Krikova; E. A. Sakharitova (Фармация и фармакология (Пятигорск))
The article reflects the features of pharmacological support of tuberculosis patients in Smolensk oblast. The participants of the process are described: the subjects of management, funding, pharmacological support. The differences between funding systems of 2008 and 2012 were characterized.